Tanzanian journalists in countering fake news: disinformation and misinformation - Dianus Ishengoma; Given Mutinta (Communicare)
The widespread dissemination of fake news, “disinformation and misinformation”, is an ongoing issue that has garnered significant attention from scholars and media professionals due to its contribution to public distrust of the credibility of news provided by media outlets. This article explores Tanzanian journalists’ efforts to combat fake news by assessing their awareness, challenges and strategies. A quantitative approach was employed to gather data from a sample of 306 journalists from radio, television, newspapers and online/digital media across various parts of Tanzania’s mainland. Data collection was facilitated through a questionnaire that incorporated closed-ended and open-ended questions, distributed via Google Forms to various online journalists’ platforms, including WhatsApp and email groups. The findings indicate that an impressive 77.8% of these journalists possess a strong understanding of “fake news” and related concepts such as disinformation and misinformation. Over 70% of respondents encountered fake story sources in their daily journalistic pursuits, with the majority acknowledging its detrimental impact on media organisation credibility. The research also revealed a reliance on traditional methods by Tanzanian journalists to counter fake story sources used. Challenges were identified, including delayed responses from experts or government officials to validate the authenticity of a given story, pressure to report breaking news, a lack of fact-checking software, unreliable Internet connectivity for verifying facts online, and a shortage of trained journalists and news gatekeepers capable of identifying fake news sources.